COMPARATIVE ANALYSIS OF ENGLISH AND UZBEK: EXPLORING LINGUISTIC PECULIARITIES - Doston Ubaydullaev Ziyodulla o’g’li; Zilola Abdurakhmanova Yoqubjon qizi (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Annotation: This comprehensive article investigates the linguistic landscape of English and Uzbek, highlighting seven key linguistic peculiarities: phonetic, phonological, grammatical, semantic, etymological, lexical, and stylistic. The exploration delves into the contrasting features of these languages, shedding light on their distinct phonetic systems, grammatical structures, and semantic nuances. The analysis extends to etymological roots, emphasizing the historical influences that have shaped their vocabulary. Furthermore, the examination of lexical variations reflects the cultural and societal contexts embedded in the languages. The article concludes by underlining the importance of understanding these linguistic peculiarities for effective communication and cross-cultural appreciation.